The flare-activity of 2MASS J16111534–1757214 in the upper Scorpius association - Guenther, E. W; Wockel, D; Chaturvedi, P; Kumar, V; Srivastava, M. K; Muheki, P (Monthly Notices of the Royal Astronomical Society, 2021)
Flares are known to play an important role for the evolution of the atmospheres of young planets. In order to understand the evolution of planets, it is thus important to study the flare-activity of young stars. This is particularly the case for young M-stars, because they are very active. We study photometrically and spectroscopically the highly active M-star 2MASS J16111534– 1757214. We show that it is a member of the Upper Sco OB association, which has an age of 5–10 Myrs. We also re-evaluate the status of other bona-fide M-stars in this region and identify 42 members. Analyzing the K2-light curves, we find that 2MASS J16111534–1757214 has, on average, one super-flare with E ≥ 1035 erg every 620 h, and one with E ≥ 1034 erg every 52 h. Although this is the most active M-star in the Upper Sco association, the power-law index of its flare-distribution is similar to that of other M-stars in this region. 2MASS J16111534–1757214 as well as other M-stars in this region show a broken power-law distribution in the flare-frequency diagram. Flares larger than E ≥ 3 1034 erg have a power-law index β = −1.3 ± 0.1 and flares smaller than that β = −0.8 ± 0.1. We furthermore conclude that the flare-energy distribution for young M-stars is not that different from solar-like stars
Keywords: Planets and satellites; Atmospheres – planets and satellites; Magnetic fields – stars; Activity – stars; Flare – stars; Individual; 2MASS J16111534–1757214 – stars; Low-mass – stars; Magnetic field.